PENGARUH LATIHAN DRILL TERHADAP AKURASI PUKULAN DROPSHOT DALAM PERMAINAN BULUTANGKISDI EKSTRAKURIKULER SMAN 1 KADUGEDE - Arif Taufik Qurohman; Dani Nurdiansyah (STKIP Subang, 2025)
PENGARUH LATIHAN DRILL TERHADAP AKURASI PUKULAN DROPSHOT DALAM PERMAINAN BULUTANGKIS DI EKSTRAKURIKULER SMAN 1 KADUGEDE. This study aims to analyze the effect of drill training on the accuracy of dropshot strokes in badminton among extracurricular students at SMAN 1 Kadugede. The research employed an experimental method with a one-group pretest–posttest design. The sample consisted of 10 students selected purposively, focusing on those who had not yet mastered the dropshot technique. The instrument used was a dropshot skill test with 10 attempts, and scores were based on shuttlecock accuracy. Data were analyzed using normality and homogeneity tests, followed by a paired sample t-test. The results showed a significant improvement, with the mean score increasing from 17.40 in the pretest to 21.80 in the posttest. The normality and homogeneity tests confirmed that the data met statistical assumptions, while the paired sample t-test yielded a significance value of 0.000 (< 0.05). This indicates that drill training had a significant effect on dropshot accuracy..